Reduction of protein‐bound uraemic toxins in plasma of chronic renal failure patients: A systematic review. (1st April 2021) - Saar‐Kovrov, V.; Zidek, W.; Orth‐Alampour, S.; Fliser, D.; Jankowski, V.; Biessen, E. A. L.; Jankowski, J.
Abstract: Background: Protein‐bound uraemic toxins (PBUTs) accumulate in patients with chronic kidney disease and impose detrimental effects on the vascular system. However, a unanimous consensus on the most optimum approach for the reduction of plasma PBUTs is still lacking. Methods: In this systematic review, we aimed to identify the most efficient clinically available plasma PBUT reduction method reported in the literature between 1980 and 2020. The literature was screened for clinical studies describing approaches to reduce the plasma concentration of known uraemic toxins. There were no limits on the number of patients studied or on the duration or design of the studies. Results: Out of 1274 identified publications, 101 studies describing therapeutic options aiming at the reduction of PBUTs in CKD patients were included in this review. We stratified the studies by the PBUTs and the duration of the analysis into acute (data from a single procedure) and longitudinal (several treatment interventions) trials. Reduction ratio (RR) was used as the measure of plasma PBUTs lowering efficiency. For indoxyl sulphate and p ‐cresyl sulphate, the highest RR in the acute studies was demonstrated for fractionated plasma separation, adsorption and dialysis system. In the longitudinal trials, supplementation of haemodialysis patients with AST‐120 (Kremezin®) adsorbent showed the highest RR. However, no superior method for the reduction of all types of PBUTs was identified based on the published studies. Conclusions: Our study shows that there is presently no technique universally suitable for optimum reduction of all PBUTs. There is a clear need for further research in this field. Abstract :